THERAPEUTIC AND NUTRITIONAL VALUE OF DRIED MELON AS A NATURAL NUTRIENT-RICH FOOD PRODUCT (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Dried melon is a traditional fruit product widely consumed in many regions of Central Asia. It is appreciated not only for its pleasant taste and long shelf life but also for its nutritional richness and potential health-promoting effects. Fresh melon contains vitamin C, provitamin A carotenoids, minerals, fiber, and various bioactive compounds, while drying reduces water content and increases nutrient density per unit weight. Melon fruits are also known to contain antioxidant compounds that may contribute to general well-being when included in a balanced diet. This article examines the nutritional composition, functional properties, and possible therapeutic significance of dried melon based on an analytical review of relevant scientific literature. The findings indicate that dried melon can be regarded as a convenient source of energy and micronutrients, although its sugar concentration after drying requires moderate consumption.
Keywords: Dried melon, natural nutrients, functional food, Cucumis melo, antioxidants, traditional food, health benefits, dehydration.